2021
DOI: 10.1002/adsc.202100142
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of 5‐Aminoimidazoles via Palladium‐Catalysed Double Isocyanide Insertion Reaction

Abstract: A palladium‐catalysed tandem cyclisation reaction of amidoximes, isocyanides and amines to produce 5‐aminoimidazoles was developed. Various 5‐aminoimidazoles were prepared in good to excellent yields under mild conditions. This elegant domino process involves the effective cleavage of the N−O bond and the formation of new C−C and C−N bonds in a single operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In 2021, Pan et al synthesized 5-aminoimidazoles 135 in moderate to high yields (57-91%) from the reaction of amidoximes 129, amines 130 and isocyanides 2 in the presence of Pd(OAc) 2 and PPh 3 in DMSO at 100 °C (Scheme 18). [35] Control experiments showed that this process started by oxidative addition of amidoximes 129 into Pd(0)L 2 (produced from the reaction of PdL 2 and PPh 3 ) to produce the palladium species 131. Then, the double insertion of two molecules of isocyanides 2 into intermediates 131 gave intermediates 132.…”
Section: Amidoximesmentioning
confidence: 99%
“…In 2021, Pan et al synthesized 5-aminoimidazoles 135 in moderate to high yields (57-91%) from the reaction of amidoximes 129, amines 130 and isocyanides 2 in the presence of Pd(OAc) 2 and PPh 3 in DMSO at 100 °C (Scheme 18). [35] Control experiments showed that this process started by oxidative addition of amidoximes 129 into Pd(0)L 2 (produced from the reaction of PdL 2 and PPh 3 ) to produce the palladium species 131. Then, the double insertion of two molecules of isocyanides 2 into intermediates 131 gave intermediates 132.…”
Section: Amidoximesmentioning
confidence: 99%
“…Pan, Sun, and co-workers reported the synthesis of 5aminoimidazole derivatives via palladium-promoted double cyanide insertion. [40] In these three-component domino reactions, amidoximes, isocyanides, and primary amines were treated with Pd(OAc) 2 and PPh 3 in DMSO to give (Z)-products 11 with medium to excellent yields (Scheme 27). These were formed in a domino process involving the cleavage of the NÀ O bond and the formation of new CÀ C and CÀ N bonds.…”
Section: Intermolecular Ring Formationsmentioning
confidence: 99%
“…Similarly, the reaction of N -sulfonyl-1,2,3-triazoles with oxadiazolone provides 5-sulfonamido-1-methyl/benzylimidazoles (Scheme 1, eqn (5)). Very recently, Wang and co-workers 54 developed an interesting synthesis method for 5-aminoimidazole derivatives via palladium-catalyzed multicomponent reactions involving amidoximes, isocyanides, and amines (Scheme 1, eqn (6)). There are currently only a few available methods for the synthesis of 5-aminoimidazoles.…”
Section: Introductionmentioning
confidence: 99%